Studies on the Consumption of eri Silkworm, Philosamia ricini Hutt. as Food in Nagaland - Imtinaro, L; Chadurvedi, D. P.; Alemla Ao, M. (International Journal of Bio-resource and Stress Management, 2023)
The purpose of rearing eri silkworm in Nagaland is mostly for its pupae which form a delicious food item for a large section of population. In the present study, survey was carried out during 2008 among the nine (9) communities in Nagaland with five (5) households selected from each community for this study. Data indicated that respondents consumed the eri worms at the pupal stage and preferred both by young and old alike and also by both the gender. Most of the respondents consumed by boiling it in bamboo shoot and also frying in oil. The study also revealed that pupae are highly in demand in the market, the rearers earned more by selling eri pupa than the cocoon. So, good market linkage through regulated market or private dealers is the need of the hour to promote eri culture in Nagaland.